2015
DOI: 10.5370/jeet.2015.10.5.2105
|View full text |Cite
|
Sign up to set email alerts
|

Study of Dielectric Properties of a Potential RBD Palm Oil and RBD Soybean Oil Mixture as Insulating Liquid in Transformer

Abstract: -This paper reported the experimental result of dielectric properties of Refined, Bleached and Deodorized Palm Oil (RBDPO) combined with 0-50% of Refined, Bleached and Deodorized Soybean Oil (RBDSO). The dielectric strength and relative permittivity of RBDPO/RBDSO was higher compared to mineral oil at all ranges of ratios and temperatures which indicated a positive sign for its possible use as insulating liquid in a transformer. All ratios of the RBDPO/RBDSO mixture also demonstrated lower dissipation factor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 44 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Rapp et al [3] have shown that the lightning impulse breakdown voltage of natural ester fluids show similar characteristics when compared with mineral oil. Dielectric characteristics of natural ester based oils have been reported in several earlier papers [4,5].…”
Section: Introductionmentioning
confidence: 95%
“…Rapp et al [3] have shown that the lightning impulse breakdown voltage of natural ester fluids show similar characteristics when compared with mineral oil. Dielectric characteristics of natural ester based oils have been reported in several earlier papers [4,5].…”
Section: Introductionmentioning
confidence: 95%
“…Blends of MI and NEI oils have been shown to have good oxidation stability, which will reduce the overall cost of transformer operation associated with frequent oil changes. The optimal mixing ratio has been shown to be 80% of MI oil and 20% of synthetic or NEI oil [23]- [25]. In this study, an attempt has been made to determine the best mixing ratio for MI-NEI oil blends in terms of the AC breakdown voltage (NEI oil is palm oil based).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable oils are among the viable alternatives of dielectric insulation fluids that have been identified for application in transformers. In recent years, a number of laboratory studies have been carried out to examine the suitability of these oils; these covered different aspects, including their dielectric, physical, and chemical properties [ 1 , 2 , 3 , 4 ]. Vegetable oils have also been tested and applied in transformers at different voltage levels [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, different types of vegetable oils have been proposed for potential application in transformers usage, such as rapeseed, sunflower, olive, castor, palm and coconut oils [ 1 , 2 , 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Several studies have also been carried out on chemically modified vegetable oils [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%